KEBIJAKAN SAFEGUARD INDONESIA MELALUI BEA MASUK TINDAKAN PENGAMANAN (BMPT) TERHADAP IMPOR KARPET ASAL CINA - Hargean "; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The government of Indonesia through the Ministry of Finance issued Ministerial Regulation number 10/PMK.010/2021 concerning the Imposition of Safeguard Measure Import Duty (BMTP) on the Import of Carpet Products and Other Textile Floor Coverings. Based on data from the Central Statistics Agency (BPS) in the last three years (2017-2019), there has been an increase in the volume of imports of carpets and other textile floor coverings with a trend of 25.2 percent. BMTP is imposed with the aim of facilitating domestic producers or industries experiencing serious losses or threats of serious losses to make the necessary adjustments. This research is theoretically constructed using a mercantilism perspective and is supported by safeguards theory. The formulation of all arguments, data, facts, and theoretical framework in this study uses a qualitative description method. This study also uses the nation-state as a level of analysis. The result of this research show import value data from 2021 to 2022 shows that the BMTP for carpets and other textile floor coverings has not been able to suppress the number of exports from China that enter. The volume of imported carpets based on weight in kilograms from 2021 to 2022 tends to increase around 581,281. Therefore, the BMTP does not reduce the import value of Carpet and Other Textile Floor Covering Products. Keywords: BMTP, carpet products and other textile floor coverings, security measures